PENYELESAIAN SENGKETA PEMELIHARAAN ANAK DI BAWAH UMUR AKIBAT PERCERAIAN OLEH PENGADILAN AGAMA DITINJAU DARI PERSPEKTIF FEMINIS YURISPRUDENCE - Hervina Puspitosari (RECHTSTAAT, 2014)
Legal issues related to child custody is parenting a child when his parents divorced. Background judge decide custody of minors is on his father, among others, if a mother is not able to provide a decent living for their child, and often act rude and not able to educate their children in either of the material, physical and spiritual.Keywords: Child Maintenance, Feminis Yurisprudence